The Impact of the Russia-Ukraine War on the Indonesian Economy - Junaedi Junaedi (Celebes Scholar pg, 2022)
The war that occurred between Russia and Ukraine also had an impact on Indonesia, the war had a fairly serious impact on Indonesia. This is because of the effects of globalization. As a result of globalization, the positive effect received by Indonesia is being able to enjoy technology that is as good as other countries and world-class education. While the negative effects of globalization, if something happens in other parts of the world, it will quickly have an impact on Indonesia including: a decrease in the rupiah exchange rate, a decline in the capital market, loss of income due to a decline in exports, the impact of rising oil prices on the state budget and an increase in imported wheat commodities. The purpose of this study is expected to be able to study and analyze the impact of the Russo-Ukrainian War on the Peace of Diplomatic Relations and the Indonesian Economic Sector. Data analysis was carried out using an analysis of the Impact of the Russo-Ukrainian War on the Indonesian Economy. Ukraine Against the Indonesian Economy. As for the benefits of this research Academically, this research is useful regarding the Impact of the Russo-Ukrainian War on the Indonesian Economy, while Theoretically, this research can enrich the literature in terms of studying the Impact of the Russo-Ukrainian War on the Indonesian Economy.